2020
DOI: 10.1073/pnas.2004900117
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of titin-based cardiac stiffness by unfolded domain oxidation (UnDOx)

Abstract: The relationship between oxidative stress and cardiac stiffness is thought to involve modifications to the giant muscle protein titin, which in turn can determine the progression of heart disease. In vitro studies have shown that S-glutathionylation and disulfide bonding of titin fragments could alter the elastic properties of titin; however, whether and where titin becomes oxidized in vivo is less certain. Here we demonstrate, using multiple models of oxidative stress in conjunction with mechanical loading, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 42 publications
(100 reference statements)
0
42
0
Order By: Relevance
“…Unfolded domain oxidation (UnDOx) within the titin filament was recently reported to alter titin-based properties 35 . Many pathologies including ischemia are linked to alterations of the oxidative state.…”
Section: Discussionmentioning
confidence: 99%
“…Unfolded domain oxidation (UnDOx) within the titin filament was recently reported to alter titin-based properties 35 . Many pathologies including ischemia are linked to alterations of the oxidative state.…”
Section: Discussionmentioning
confidence: 99%
“…In case of the giant muscle protein titin, reversible oxidation was recently shown to reduce the protein's elasticity through preferential modification of mechanosensitive Ig domains in the I‐band region of the muscle sarcomere (Loescher et al , 2020 ). This process, termed unfolded domain oxidation (UnDOx), increases cardiac stiffness under mechanical force and oxidative stress.…”
Section: Protein Triage Under Mechanical Stressmentioning
confidence: 99%
“…In addition to the reported correlation between phosphorylation changes and diastolic heart function (Chiao et al, 2020), there are indications that oxidative changes may also contribute to elamipretide's improvement of diastolic function in aged hearts. A recent study has revealed that cardiac stiffness is heavily influenced by the oxidation of cysteine residues along titin (Loescher et al, 2020), and many of these same residues showed enhanced S-glutathionylation with age that was reversed by elamipretide treatment in our analysis. The combined lower oxidation of essential mitochondrial and cardiac proteins may be one of the core mechanisms by which elamipretide is able to drastically improve the function of aged hearts.…”
Section: Mitochondrial Thiols Are Heavily Oxidized With Age But Elamipretide Rapidly Reverses These Changesmentioning
confidence: 53%